Plant defence allocation patterns following an increasing water level gradient in a freshwater wetland. (December 2019) - Shan, Liping; Song, Changchun; Zhang, Xinhou; Cagle, Grace Ann; Shi, Fuxi
Graphical abstract: Highlights: Plants can alter the allocation of defences in response to increasing water level. Both flood-sensitive and flood-tolerant species were selected. Plant chemical and structural defence strategies vary by tissue. Plant leaves can be better chemical defended than other tissues. Plant defence allocation can indicate plant distribution in freshwater wetlands. Abstract: Plant species are characterized by high adaptability to water level fluctuation in freshwater wetlands. Alteration in defence allocation patterns is one of the plant defence strategies in response to increasing water level gradients. Two dominant species, flood-sensitive species Deyeuxia angustifolia and flood-tolerant species Carex pseudocuraica, from freshwater marshes in the Sanjiang Plain were collected and treated with four water level gradients (–5, 0, 5, and 15 cm, relative to the soil surface), and both plant chemical (total polyphenols and condensed tannins) and structural (cellulose and lignin) defence compounds in leaves, stems and roots were measured. Increasing water level significantly decreased concentration of condensed tannins in C. pseudocuraica roots. For structural defence compounds, lignin concentration in C. pseudocuraica roots increased, which performed the contrary results in D. angustifolia roots and leaves. On the whole plant level, concentrations of chemical defence compounds in plant leaves were higher than that in stems and roots. Moreover, both the total phenols allocation to D. angustifolia leaves and condensed tannins allocation to C. pseudocuraica roots decreased with the increasing water level. Negative correlations between concentrations of condensed tannins and cellulose could be found in both D. angustifolia and C. pseudocuraica leaves. Plants adopt different defence strategies in response to the increasing water level, which provide us new purviews for revealing the plant distribution patterns in freshwater wetlands.